Transcribed ultraconserved region (T-UCR) uc.261 expression is closely correlated with disease activity and intestinal permeability in Crohn's disease. (October 2019) - Qian, Xiao-Xian; Cai, Chen-Wen; Li, Han-Yang; Lai, Li-Jie; Song, Dong-Juan; Qiao, Yu-Qi; Shen, Jun; Ran, Zhi-Hua
Objectives: Transcribed ultraconserved region (T-UCR) uc.261 is reported to participate in intestinal mucosa barrier damage in Crohn's disease (CD). The aim of this study was to determine the association with disease activity and intestinal permeability. Methods: Uc.261 level in colon mucosa and Harvey-Bradshaw Index (HBI) were evaluated in 20 active CD patients. Uc.261 expression and transepithelial electrical resistance (TEER) were determined in Caco2 and T84 cells treated with tumor necrosis factor alpha (TNF-α), respectively. Body weight, disease activity index (DAI), colon length, histological index (HI), intestinal permeability to FITC-dextran, uc.261, and tight junction proteins (TJPs) levels were evaluated in BALB/C mice treated with saline enema, trinitrobenzene sulfonic acid (TNBS)/ethanol enema, and anti-TNF-α monoclonal antibody injection, respectively. Results: Uc.261 expression was overexpressed in CD patients, TNF-α treated cells, and colitis mice. Uc.261 expression was positively correlated with HBI ( r  = 0.582, p  = 0.007) in CD patients, and positively correlated with TNF-α concentration and negatively correlated TEER in Caco2 and T84 cells (all p  < 0.05). Furthermore, uc.261 was positively correlated with DAI ( r  = 0.824, p  = 0.008), HI ( r  = 0.672, p  = 0.021), and intestinal permeability ( r  = 0.636, p  = 0.012), while negatively correlated with body weight ( r  = –0.574, p  = 0.035), colon length ( r  = –0.866, p  = 0.017), and TJP expression (all p  < 0.05) in colitis mice. Conclusions: Uc.261 expression was closely correlated with disease activity and intestinal permeability in CD. Anti-TNF-α treatment may play its role through suppressing uc.261 expression in colitis mice.